2023
DOI: 10.1002/jia2.26060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on mental health, associated factors and coping strategies in people living with HIV: a scoping review

Abstract: Introduction:The COVID-19 pandemic and associated measures implemented by authorities have created additional stressors and increased the risk of psychological illnesses among people living with HIV (PLWH). Yet, there is no collective evidence on the mental health status of this population during the global pandemic and associated factors. This scoping review aimed to synthesize the evidence in the current literature related to the mental health outcomes and challenges faced by PLWH during the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…To our knowledge, our study is among the first to examine the association between violence victimization and SMI among PWUOs. These findings add additional evidence to the literature and echo previous studies indicating the impact of violence victimization and mental health outcomes among various populations, including sexual and gender minority and people living with HIV (Brown et al, 2016;Buller et al, 2014;Finneran & Stephenson, 2013;Hong et al, 2023). We also found that having SMI was associated with multilevel factors, including individual factors such as being female, identifying as bisexual, lower income and being unemployed, and structural barriers, such as having resource negotiation history and being incarcerated.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, our study is among the first to examine the association between violence victimization and SMI among PWUOs. These findings add additional evidence to the literature and echo previous studies indicating the impact of violence victimization and mental health outcomes among various populations, including sexual and gender minority and people living with HIV (Brown et al, 2016;Buller et al, 2014;Finneran & Stephenson, 2013;Hong et al, 2023). We also found that having SMI was associated with multilevel factors, including individual factors such as being female, identifying as bisexual, lower income and being unemployed, and structural barriers, such as having resource negotiation history and being incarcerated.…”
Section: Discussionsupporting
confidence: 87%
“…The COVID-19 pandemic brought heightened awareness to infectious diseases, which could humanize the experience of living with infections, such as HIV. However, syndemics of mental health disorders, drug use, and STIs have become exacerbated due to a variety of challenges including lack of access to health care (Hong et al, 2023). This disconnection from healthcare services could have resulted in decreased education about HIV or other conditions aside from COVID-19, which could influence attitudes and perceptions, and amplify existing disparities, as seen in one case study from Canada (Bowles et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the latter group of participants described difficulties accessing providers and canceled/delayed appointments; these participants also reported significantly more depressive symptoms than those reporting care continuity. Although several studies reported increases in depressive and other mental health symptoms during COVID-19, this was largely attributed to social isolation and economic concerns (Hong et al, 2023; Winwood et al, 2021). Our mixed-methods results suggest that lack of care continuity may also be a stressor that in turn, negatively impacts mental health.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential translation of individual strategies between the syndemics of HIV and COVID-19 has received less attention. Instead, studies among individual PLWH have focused on challenges they faced in the context of COVID-19, like increasing mental health symptoms, social isolation, food insecurity, and socioeconomic stress (Hong et al, 2023; Meyer et al, 2023; Winwood et al, 2021; Wion & Miller, 2021). Conversely, few studies have examined strengths PLWH could leverage in a new public health crisis, despite evidence that PLWH translated some HIV self-management strategies to the COVID-19 pandemic.…”
mentioning
confidence: 99%